SEXUAL HARASSMENT AND SEXTORTION IN UNIVERSITIES AS AN ACTUAL SCIENTIFIC PROBLEM - Olena Druhanova; Alina Fedonenko; Oleksii Nalyvaiko (Borys Grinchenko Kyiv Metropolitan University, 2022)
This article explores the issues of harassment in the university environment. The concept of sextortion in education would be taken as a basis. This problem is now being actively studied by scientists from all over the world, which indicates its importance and attempts to scientifically substantiate ways to prevent and fight this phenomenon. The study also focuses on aspects of the cultural manifestation of this illegal phenomenon in education, namely cinema and the media. The most important factor that declares the importance of a particular phenomenon in society is its reflection in popular culture and its discourse. The problem of sextortion in education is undoubtedly such. It should be clarified that this applies mainly to the countries of the Western world, but in Ukraine this problem is also very relevant in the educational environment of universities. The article provides specific examples of inappropriate sexual behavior in educational institutions and analyzes the problem from various sides and subjects of involvement. In addition, the very concept of sextortion and its genesis are analyzed. The study cites the factors that most often lead to the manifestation of sextortion in education. In addition to all of the above, the consequences of this phenomenon on the part of the victim are analyzed, where the key consequence of sexual claims is the impact on the emotional state of a person: victim becomes more vulnerable and feels insecure, being in eternal fear. Is it normal when a future specialist, mastering his profession, cannot feel calm? The authors also offer recommendations for countering and preventing this phenomenon in the university environment with an emphasis on preventive measures, but with the observance of procedures to avoid slander and denunciations of objectionable participants in the educational process.